Settling Hebron : Jewish fundamentalism in a Palestinian city - Neuman, Tamara (Ethnography of political violence., 2018)
In Settling Hebron, Tamara Neuman presents the first critical ethnography of the Jewish settler populations in Kiryat Arba and the adjacent Jewish Quarter in the Old City of Hebron, considered by many Israelis as the most ""ideological"" of settlements.